[N `-(5-Bromo-2-oxidobenzylidene-kappa O)-3-hydroxy-2-naphthohydrazidato-kappa N-2 `,O]dimethyltin(IV) - Lee, S.M.; Ali, H.M.; Lo, K.M. (International Union of Crystallography, 2010)
The Sn-IV atom in the title compound, [Sn(CH3)(2)(C18H11BrN2O3)], shows a distorted cis-C2NO2Sn trigonal-bipyramidal coordination geometry, with an axial O-Sn-O angle of 155.27 (9)degrees. The presence of an intramolecular O-H center dot center dot center dot N hydrogen bond between the amido N atom and hydroxy H atom in the Schiff base ligand helps to stabilize the overall molecular structure.